Nature-inspired biodegradation of poly(butylene succinate-co-adipate): the potential of Cladosporium psychrotolerans isolated from marine copepods - Luca Niccolini; Giampiero De Simone; Maurizia Seggiani; Niccoletta Barbani; Damiano Rossi; Miriam Cappello; David Levin; Federica Spina; Xiaojun Yan; Giulio Petroni; Isabella Buttino; Simona Di Gregorio (Environmental Science and Pollution Research, 2025)

A Snapshot of the Taxonomic Composition and Metabolic Activity of the Microbial Community in an Arctic Harbour (Ny-Ålesund, Kongsfjorden, Svalbard) - Simone Cappello; Francesco Smedile; Gabriella Caruso; Sabrina Patania; Alessia Lunetta; Maurizio Azzaro (Journal of Marine Science and Engineering, 2023)
Within the Svalbard archipelago, Kongsfjorden is an important marine ecosystem that is recognised as one of the main representative Arctic glacial fjords. Prokaryotic organisms are key drivers of important ecological processes such as carbon fluxes, nutrient mineralisation, and energy transfer, as well as sentinels of environmental pollution, especially in sediments, that are a repository of contaminants. In some areas of the Arctic, the structure and metabolic activity of the microbial community in the organic matter turnover and globally in the functioning of the benthic domain are mostly still unknown. A snapshot of the main microbial parameters such as bacterial abundance (by microscopic and plate counts), structure (by 16S rRNA sequencing), and metabolic activity was provided in Ny-Ålesund harbour, contextually in seawater and sediment samples. Fluorogenic substrates were used to assess the microbial ability to utilise organic substrates such as proteins, polysaccharides, and organic phosphates through specific enzymatic assays (leucine aminopeptidase—LAP, beta-glucosidase—ß-GLU, and alkaline phosphatase—AP, respectively). The metabolic profiles of psychrophilic heterotrophic bacterial isolates were also screened using a qualitative assay. The phylogenetic analysis of the microbial community revealed that Proteobacteria prevailed among the observed taxonomic groups. Several of the observed sequences were assigned to clones found in harbours, microbial biofilms, antifouling paints, or oil-polluted facilities of cold environments, highlighting a signature of human pressure on the polar habitat of Ny-Ålesund harbour.

Thermophilic Hydrocarbon-Utilizing Bacilli from Marine Shallow Hydrothermal Vents as Producers of Biosurfactants - Vincenzo Zammuto; Antonio Spanò; Marco Sebastiano Nicolò; Emanuela Grillo; Maria Teresa Caccamo; Salvatore Magazù; Simone Cappello; Concetta Gugliandolo (Journal of Marine Science and Engineering, 2022)
The exploitation of thermophilic hydrocarbon-utilizing bacilli could provide novel environmentally friendly surfactants. In this work, 80 thermophilic bacilli isolated from shallow hydrothermal vents of the Eolian Islands (Italy) were screened for their ability to utilize hydrocarbons and produce biosurfactants (BSs). Among them, 15 strains grew with kerosene or gasoline (2% v/v) as the only carbon and energy source, and most of them were positive to the methylene blue agar as prescreening assay for BSs production and displayed emulsifying activity. The cell-free supernatants (CFSs) from two selected strains, Bacillus licheniformis B3-15 and Bacillus horneckiae SBP3, were both surface active and able to emulsify different hydrocarbons and vegetable oils. BSs from B3-15 (910 mg L−1) and SBP3 (950 mg L−1) were chemically different surfactin-like lipopeptides, with specific mineral-, castor- and crude oil removal ability from the cotton matrix. CFSs from the 15 thermophilic strains, which harbor both lipolytic and surfactant abilities, could be suitable for industrial-based applications and environmental issues, such as oil recovery and removal from polluted areas or surfaces, (e.g., oil pipelines, bilge tankers, or industrial silos), whereas the crude BSs, as high-value compounds, may be used in different fields of application, as detergent, cosmeceutical, and pharmaceutical industries.

Effect of glyphosate and paraquat on seed germination, amino acids, photosynthetic pigments and plant morphology of Vicia faba, Phaseolus vulgaris and Sorghum bicolor - Mohamed Maldani; Fatima Zahra Aliyat; Simone Cappello; Marina Morabito; Filippo Giarratana; Laila Nassiri; Jamal Ibijbijen (Environmental Sustainability, 2021)

Effects of Pesticides Use (Glyphosate & Paraquat) on Biological Nitrogen Fixation - Maldani Mohamed; Fatima Zahra Aliyat; Btissam Ben Messaoud; Cappello Simone; Morabito Marina; Giarratana Filippo; Nassiri Laila; Ibijbijen Jamal (Water, Air, & Soil Pollution, 2021)

Phenotypic Variations of Oleispira antarctica RB-8(T) in Different Growth Conditions - Gabriella Gentile; Giovanna Maimone; Rosabruna La Ferla; Maurizio Azzaro; Maurizio Catalfamo; Maria Genovese; Santina Santisi; Mohamed Maldani; Angela Macrì; Simone Cappello (Current Microbiology, 2020)

Assessing the Effect of Contaminated and Restored Marine Sediments in Different Experimental Mesocosms Using an Integrated Approach and Mytilus galloprovincialis as a Model - Stefania Ancora; Federica Rossi; Marina Borgese; Cristina Pirrone; Ilaria Caliani; Simone Cappello; Giuseppe Mancini; Nicola Bianchi; Claudio Leonzio; Giovanni Bernardini; Rosalba Gornati (Marine Biotechnology, 2020)

Mesocosm System to Evaluate BF-MBR Efficacy in Mitigating Oily Wastewater Discharges: an Integrated Study on Mytilus galloprovincialis - Rosalba Gornati; Maria Maisano; Cristina Pirrone; Tiziana Cappello; Federica Rossi; Marina Borgese; Alessia Giannetto; Simone Cappello; Giuseppe Mancini; Giovanni Bernardini; Salvatore Fasulo (Marine Biotechnology, 2019)

Effects of microplastics on trophic parameters, abundance and metabolic activities of seawater and fish gut bacteria in mesocosm conditions - Gabriella Caruso; Cristina Pedà; Simone Cappello; Marcella Leonardi; Rosabruna La Ferla; Angelina Lo Giudice; Giulia Maricchiolo; Carmen Rizzo; Giovanna Maimone; Alessandro Ciro Rappazzo; Lucrezia Genovese; Teresa Romeo (Environmental Science and Pollution Research, 2018)

Shell fluctuating asymmetry in the sea-dwelling benthic bivalve Mytilus galloprovincialis (Lamarck, 1819) as morphological markers to detect environmental chemical contamination - Massimiliano Scalici; Lorenzo Traversetti; Federica Spani; Valentina Malafoglia; Monica Colamartino; Tiziana Persichini; Simone Cappello; Giuseppe Mancini; Giulia Guerriero; Marco Colasanti (Ecotoxicology, 2017)

Regulation of Langerhans cell functions in a hypoxic environment - Daniele Pierobon; Federica Raggi; Irene Cambieri; Simone Pelassa; Sergio Occhipinti; Paola Cappello; Francesco Novelli; Tiziana Musso; Alessandra Eva; Carlotta Castagnoli; Luigi Varesio; Mirella Giovarelli; et al. (Journal of Molecular Medicine, 2016)

Synthesis of water suitable as the MEPC.174(58) G8 influent water for testing ballast water management systems - Fabio D’Agostino; Marianna Del Core; Simone Cappello; Salvatore Mazzola; Mario Sprovieri (Environmental Monitoring and Assessment, 2015)

The “SYSTEMS BIOLOGY” in the study of xenobiotic effects on marine organisms for evaluation of the environmental health status: biotechnological applications for potential recovery strategies - Salvatore Fasulo; Giulia Guerriero; Simone Cappello; Marco Colasanti; Trifone Schettino; Claudio Leonzio; Giuseppe Mancini; Rosalba Gornati (Reviews in Environmental Science and Bio/Technology, 2015)

STRANgE, integrated physical–biological–mechanical system for recovery in of the “oil spill” in Antarctic environment - Simone Cappello; Giuseppe Mancini; Alessandro Pistone; Maurizio Azzaro; Francesco Bottino; Lucrezia Genovese; Daniela Iannazzo; Antonella Luciano; Antonino Mamo; Giovanni Neri; Signorino Galvagno; Santina Santisi; et al. (Reviews in Environmental Science and Bio/Technology, 2014)

Natural microbial diversity in superficial sediments of Milazzo Harbor (Sicily) and community successions during microcosm enrichment with various hydrocarbons - Michail M. Yakimov; Renata Denaro; Maria Genovese; Simone Cappello; Giuseppe D’Auria; Tatyana N. Chernikova; Kenneth N. Timmis; Peter N. Golyshin; Laura Giluliano (Environmental Microbiology, 2005)
Summary Hydrocarbon‐contaminated superficial sediments collected from the Harbor of Milazzo (Tirrenean Sea, northern Sicily), a zone strongly affected by anthropogenic activities, were examined for in situ biodegradative capacities. A culture‐independent molecular phylogenetic approach was used to study the influence of hydrocarbon and nutrient addition on the activity and diversity of the indigenous microbiota during a microcosm evaluation. The autochthonous microbial community in non‐polluted sediments was represented by eubacterial phylotypes grouped within Proteobacteria , CFB and Firmicutes . The archaeal domain was represented by members of Marine Group I of Crenarchaeota . The majority of recovered sequences was affiliated with heterotrophic genera Clostridium and Vibrio , typical members of eutrophic coastal environments. Amendments of hydrocarbons and mineral nutrients to microcosms dramatically changed the initial diversity of the microbial community. Only bacterial phylotypes affiliated with Proteobacteria and CFB division were detected. The decrease in diversity observed in several microcosms could be explained by the strong selection for microorganisms belonging to group of marine hydrocarbonoclastic γ‐ Proteobacteria , namely Alcanivorax , Cycloclasticus , Marinobacter , Marinobacterium/Neptunomonas and Thalassolituus . This study demonstrated that nutrient amendment to hydrocarbon‐contaminated superficial sediments enhanced the indigenous microbial biodegradation activity and that highly specialized marine hydrocarbonoclastic bacteria, representing a minor fraction in the natural microbial community, play an important role in the biodegradation of petroleum hydrocarbons accidentally entering the coastal environment.